Integrating Maqāṣid al-Shariah, ESG, and Halālan Ṭayyiban in Indonesia: A TCCM-Based Systematic Literature Review and Bibliometric Analysis - Azy Athoillah Yazid; Moch Mahsun; Raihan Nasir (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2026)
Introduction: This study maps the intellectual landscape of Environmental, Social, and Governance (ESG) integration within the Indonesian economic and financial markets to establish a comprehensive halālan ṭayyiban ecosystem. Methods: A framework-based systematic literature review was conducted using the Theory, Context, Characteristics, and Method (TCCM) approach, combined with bibliometric analysis via R to examine halal-ESG-sustainability literature published between 2014 and 2025. Results: The findings reveal that existing literature predominantly focuses on normative-legal and compliance aspects, particularly halal certification, while operational environmental sustainability and halal-ecology integration remain underexplored. This thematic polarization indicates that extensive research is currently directed towards conceptual legitimacy, implementation, measurement, and institutional structures, which ultimately facilitates systemic integration. Consequently, this study formulates a theoretical model integrating Maqāṣid, ESG, and Halālan Ṭayyiban principles to synthesize inter-dimensional relationships, empirical findings, and implementation indicators. Conclusion and suggestion: Practically, the results highlight a critical need to transition from administrative compliance to operational capacity-building, particularly concerning Micro, Small, and Medium Enterprises (MSMEs), system governance, and infrastructure traceability. To bridge the gap between normative frameworks and practical alignment, future research must prioritize integrated performance indicators, implementative intervention designs, and cross-national comparative studies, thereby addressing current limitations regarding corpus metadata dependency and exploratory projections.